A personalised semantic and spatial information retrieval system based on user's modelling and accessibility measure. (1st January 2014) - Baazaoui, Hajer; Haddad, Mohamed Ramzi; Ghezala, Henda Ben
Search personalisation is a multi-criteria decision problem whose objective is to filter out relevant information based on a set of criteria. Web personalisation can be seen as an interdisciplinary field whose objective is to facilitate the interaction between web content and users' needs. The personalised search focuses on integrating users' contexts, needs and relevancy criteria in the information retrieval process. This paper presents user's modelling for personalised spatial and semantic information retrieval. The idea is to provide a user with personalised results based on his model and on the neighbour users' models. The spatial personalisation search is based on a measure of spatial accessibility, whose objective is to predict and evaluate location relevancy, accessibility as well as associations at the user level. Experiments confirm the effectiveness of our proposal by pointing out the improvement of the personalised search results when compared to a baseline web search.